Mathematical Analysis on the Effects of Microplastic Pollution and Ocean Acidification on Coral Reefs in Aquatic Ecosystem - Rahman, MD Shakilur; Mallick, Uzzwal Kumar (Jambura Journal of Biomathematics (JJBM), 2025)
This study explores the complex interplay between microplastic contamination and ocean acidiﬁcation in inﬂuencing coral reef ecosystems through the development of a mathematical model with time-varying parameters.  The model ensures positivity and boundedness to accurately represent ecological dynamics, and stability analyses provide insights into system behavior under various environmental conditions.  Numerical simulations validate the theoretical results and reveal that microplastic accumulation in marine environments signiﬁcantly hinders coral reef establishment while contributing to elevated oceanic carbon dioxide levels. These rising CO2  levels, primarily driven by anthropogenic emissions, lead to accelerated ocean acidiﬁcation, further degrading coral reefs. Model predictions indicate that, if unchecked, the current trends in microplastic pollution and ocean acidiﬁcation will result in a 50% reduction in coral reef coverage within  four decades. However, the ﬁndings suggest that limiting microplastic input into aquatic ecosystems could  mitigate these adverse effects, preserving reef health and slowing acidiﬁcation.   By quantifying the  relationship between microplastic pollution, ocean acidiﬁcation, and coral reef dynamics, this study provides a robust framework for understanding and addressing critical threats to marine ecosystems.